Abdominal aortic aneurysms: A little known risk - Giménez, José Luís (2010)
The abdominal aortic aneurysm is a frequent pathology in the current practice of a Vascular Surgery Department. It is most prevalent in men, being frequently associated with advanced age, smoking, and it is, most often, asymptomatic. Its morbi-mortality is high, and recognising its risk factors and providing an adequate follow-up will allow an improvement in the prognosis of the natural evolution of this condition: rupture and, in most cases, death.